Unlocking teaching potential: Dataset on the impact of the STAR technique in junior high microteaching for writing instruction - A.B. Prabowo Kusumo Adi; Ririn Ambarini (Social Sciences and Humanities Open)
This study evaluates the STAR technique (Strategic, Tactical, Active, and Responsive) for enhancing writing instruction in junior high school English microteaching. Using a mixed-methods approach, the research integrates quantitative performance data from 100 student teachers at Universitas PGRI Semarang with qualitative insights from interviews and classroom observations. The findings show significant improvements in teaching proficiency, demonstrating the STAR framework's effectiveness in addressing challenges in teacher education. The study emphasizes transparency, reproducibility, and open science, aligning with the FAIR Data Principles, and offers valuable insights for advancing teacher training programs and improving instructional practices in English writing.